The Combination of Criminal Acts (Ta'addud Al-Jara'im) in the Perspective of Fiqh Jinayah - Gita Ayu Maijani; Fauzan Azhima; Alya Zakira Harahap (ISNU Sumatera Utara, 2024)
A combined criminal act is a situation when a person commits more than one criminal act before there is a legal decision with permanent force. In Islamic criminal law, this concept is known as ta'addud al-jarā'im. This research aims to examine the definition, legal basis, elements, forms, criminal system, and application of punishment to a combination of criminal acts in the perspective of fiqh jinayah and positive criminal law in Indonesia. The method used is library research with a descriptive-analytical approach through the study of the Qur'an, hadith, fiqh jinayah literature, and relevant laws and regulations. The results of the study show that the combined criminal acts have a strong legal basis in Islam that emphasizes the principles of justice, accountability, and benefit. The combined forms of criminal acts include idealistic concursus, realist concursus, and continuing acts. In the application of Islamic criminal law, punishment can be in the form of hudud, qishash and diyat, as well as ta'zir by considering the rights of Allah, human rights, and the benefit of society. The difference in the views of scholars regarding the application of punishment shows the flexibility of Islamic law in dealing with various forms of crime. Thus, the rules regarding combined criminal acts reflect the perfection of the Islamic legal system which is oriented towards justice, protection of the community, and the prevention of repeat crimes.must be written with